Typescript copy of "Genreral Lucas" from an "Old comrade, Attie Hallinan"
Contains 3 copies.
Keywords: Lucas, Cuthbert Henry Tyndall -- Brigadier General -- 1879-1958; Ireland -- History; Ireland -- History -- Autonomy and independence movements